ANALISIS PENGAMBILAN KEPUTUSAN KEUANGAN DAN BISNIS PADA PERUSAHAAN PROPERTY AND REAL ESTATE - Nursasi, Enggar (Fakultas Ekonomi, UIN Maliki Malang, 2013)
This study aimed to determine whether there was a difference for firms with managerial ownership and firms with no managerial ownership in financial decision making and business decision-making. Financial decisions proxied by debt policy and business decisions proxied by the value of the company. Debt policy is indicated by the ratio of total debt to total assets (Debt to Total Assets Ratio / DTA), while commonly indicated enterprise value of Price To Book Value. The samples in this study were 112 Real Estate And Property companies are Go Gublic in BEI for the years 2008 through 2010. Hypothesis testing using t-test with a significant level of 0.015 to 0.000 for the debt policy and firm value. This suggests that there are differences in the value of corporate debt policy and for firms with managerial ownership and firm without managerial ownership.